Comparing 16S rDNA amplicon sequencing and hybridization capture for pea aphid microbiota diversity analysis - Marie Cariou; Céline Ribière; Stéphanie Morlière; Jean-Pierre Gauthier; Jean-Christophe Simon; Pierre Peyret; Sylvain Charlat (BMC Research Notes, 2018)
Abstract Objective Targeted sequencing of 16S rDNA amplicons is routinely used for microbial community profiling but this method suffers several limitations such as bias affinity of universal primers and short read size. Gene capture by hybridization represents a promising alternative. Here we used a metagenomic extract from the pea aphid Acyrthosiphon pisum to compare the performances of two widely used PCR primer pairs with DNA capture, based on solution hybrid selection. Results All methods produced an exhaustive description of the 8 bacterial taxa known to be present in this sample. In addition, the methods yielded similar quantitative results, with the number of reads strongly correlating with quantitative PCR controls. Both methods can thus be considered as qualitatively and quantitatively robust on such a sample with low microbial complexity.